1989
DOI: 10.1007/bf00378962
|View full text |Cite
|
Sign up to set email alerts
|

The effects of enriched CO2 atmospheres on plant-insect herbivore interactions: growth responses of larvae of the specialist butterfly, Junonia coenia (Lepidoptera: Nymphalidae)

Abstract: Little is known about the effects of enriched CO environments, which are anticipated to exist in the next century, on natural plant-insect herbivore interactions. To begin to understand such effects on insect growth and survival, I reared both early and penultimate instar larvae of the buckeye, Junonia coenia (Lepidoptera: Nymphalidae), on leaves from one of their major hostplants, plantain, Plantago lanceolata (Plantaginaceae), grown in either ambient (350 PPM) or high (700 PPM) CO atmospheres. Despite consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 51 publications
4
62
1
Order By: Relevance
“…Other studies similarly found no difference in larval survival under different CO 2 regimes (Osbrink, Trumble & Wagner 1987;Akey & Kimball 1989;Fajer 1989), though increased mortality under elevated CO 2 can be found when plant nitrogen is very low (Fajer, Bowers & Bazzaz 1989). Our larvae reared on plants grown under elevated CO 2 conditions were heavier in both early and final larval instars.…”
Section: Effects Of Co 2 On Plant Quality To Herbivores and Herbivoresupporting
confidence: 46%
“…Other studies similarly found no difference in larval survival under different CO 2 regimes (Osbrink, Trumble & Wagner 1987;Akey & Kimball 1989;Fajer 1989), though increased mortality under elevated CO 2 can be found when plant nitrogen is very low (Fajer, Bowers & Bazzaz 1989). Our larvae reared on plants grown under elevated CO 2 conditions were heavier in both early and final larval instars.…”
Section: Effects Of Co 2 On Plant Quality To Herbivores and Herbivoresupporting
confidence: 46%
“…At the higher levels of CO 2 the larvae were required to consume a greater quantity of leaf in order to maintain sufficient N intake. A similar response has been shown by the larvae of Junonia coema (Lepidoptera: Nymphalidae) feeding on Plantago lanceolata (Fajer 1989). Fajer et al (1989) have suggested that a lower availability of quality food may be the major response to COz relevant to herbivorous insect larvae, and could result in smaller larvae, less capable of defending themselves, and in larvae which may find it difficult to complete their development when other conditions are unfavourable (Fajer 1989).…”
Section: Herbivory Insects Fungi and Rhizobiamentioning
confidence: 60%
“…As an example, consider the effects of the CO 2 × temperature interaction on a typical plant-herbivorous insect feeding relationship, which was the most commonly examined trophic relationship across the studies we analyzed. Plant quality from the perspective of herbivorous insects is generally determined by the nutrient profile of the plant (particularly the C:N ratio for nitrogen limited insects [59,60]), any defensive chemical compounds produced by the plant (e.g., phenolics and terpenes), and the physical traits of plant tissues (e.g., leaf toughness and thickness [22]). In general, plants raised in environments with high concentrations of CO 2 exhibit high C:N ratios, increased production of phenolics, and increased leaf toughness and thickness [21,22].…”
Section: Discussionmentioning
confidence: 99%